Influence of advanced markets on the Malaysian Market - Othman Yong (Penerbit Universiti Kebangsaan Malaysia, 1994)
There is a general belief among investors and speculators in Malaysia that a small and thinly traded stock market (or an emerging market), such as the Malaysian market,is highly influenced by the big and advanced markets of the US and Japan. Specifically, this paper looks at the influence of the US (NYSE) and the Japanese (TSE) markets, on the Malaysian (KLSE) market. This study uses end-of-the-week Index changes (friday's and Saturday's performance of the US and Japanese markets, respectively) of the advanced markets and the begining-of-the-week (monday's performance of the Malaysian market) Index changes of the emerging market for a period from January 1983 to December 1990 In general, the results indicate some validity in the claim that the advanced markets of the US and Japan do influence the Malaysian market. However, the influence is not stable over time.